Honeybees as pollinators and their conservation: A review - Neelam Kumari; Dinesh Kumar; Shwata Bhatia; Shivani Seraik; Ritu Sharma (International Journal of Insects, 2024)
Pollination is a critical mechanism for maintaining and conserving biodiversity, with pollinator diversity playing a major role for the enhancement of food security and livelihoods. Pollinators provide the essential service of enabling plants to produce fruits and seeds in our ecosystems. These pollinators come from many groups within the kingdom Animala, including insects, birds, bats and reptiles. Among them, arthropods, especially honey bees, are pivotal In delivering pollination services to flowering plants. Additional important pollinators include halictids, carpenter bees, bumblebees, megachilids, andrenids, syrphids etc. Bees visit plants to obtain their food, nectar and pollen and also attracted by nectars rich in sugar content and pollens with higher nutritive values. Four important species of honey bees (Hymenoptera: Apidae) found in India: Apis cerana, Apis dorsata, Apis florae and Apis andreniformes. The two most common pollinators of vegetables and horticultural crops are the Indian hive bee, Apis cerana, and the rock bee, Apis dorsata. Declines of pollinator population are a serious global issue that has attracted the attention of experts, decision-makers and the general public. Nevertheless, parasitic mites, diseases of honey bees and the less survival of honey bees to unfavourable weather conditions are some of the difficulties that affect modern beekeeping. To effectively implement initiatives for pollinator conservation and habitat restoration there should be collaboration among governments, legislators, corporations, scientists, farmers and citizens globally. These difficulties jeopardise honeybees' overall value as pollinators. As a result, safeguarding honey bee biodiversity and wild pollinators is vital for maximising the potential yields of varied agricultural and horticultural products, developing hybrid seeds, growing crops in poly-houses, and preserving the country's rare and distinctive species.
Keywords: Beekeeping; Honey Bees; Pollination; Pollinators; conservation